Temple Grandin [videorecording (DVD)] - Jackson, Mick; Jackson, Mick; Danes, Claire, 1979-; O'Hara, Catherine; Strathairn, David; Ormond, Julia; Grandin, Temple; Grandin, Temple (HBO Home Entertainment ; Distributed by Warner Home Video, 2010)
An engaging portrait of an autistic young woman who became, through timely mentoring and sheer force of will, one of America's most remarkable success stories.